Discussion of university education in Library and Information Science: beyond Bologna - Tejada-Artigas, Carlos (Anuario ThinkEPI, 2010)
In a time of change in the Spanish universities because of the Bologna reform process, a positioning strategy of our degrees that respond to the current professional situation is required. International trends show that flexibility and cooperation with other disciplines are key in designing educational programs at the university.